Poland's enterprise environment: A Polish view - Ewa Balcerowicz (The Research Institute of the Finnish Economy (ETLA), 2006)
The paper briefly presents environment for business in Poland as of the end of the year 2005. A few comments, however, on its evolution in the course of the transition period are also made. The paper broaches administrative, legal and financial requirements to start and run business activities by both natural and legal persons. In addition, it presents government support schemes for investors. A brief description of the scope of the grey economy and corruption completes the picture of the business environment. The topic has been approached from the foreign investor's perspective. Although foreign investors are subject to the same laws as domestic (Polish) ones, in a limited number of cases they are treated differently than the latter. These cases, and specifically land purchase and employment of foreign citizens, are reviewed.
Keywords: 330; Business climate; industrial policy; state aid; grey economy; Poland; Geschäftsklima; Unternehmen; Standortpolitik; Übergangswirtschaft; Polen